Hubungan Penggunaan Media Sosial (Gadget) Dengan Kualitas Tidur Mahasiswa Universitas Widya Nusantara - Salpa, Salpa; Mulki, Moh Malikul; Elfiyunai, Ni Nyoman (Universitas Pahlawan Tuanku Tambusai, 2024)
Students are very risk of poor sleep quality, and one of the causes is excessive use of social media. Social media problems can cause sleep disorders, visual disturbances, and psychological disorders such as stress and depression. Good sleep quality will result in freshness and fitness when awakened. Preliminary studies conducted on Widya Nusantara University 3rd year students in semester 6 said that the use of gadgets is more often, even after coming back from campus they start to use gadgets from 16:00-00:00 and some even from 16:00-02:00, and social media accessed such as WhatsApp, Instagram, TikTok, Youtube, and Facebook. The aim of the research was to analyze the correlation between the use of social media (gadgets) and the student’s quality of sleep at Widya Nusantara University. This is a quantitative research method with an analytical approach using a cross-sectional research design that was conducted on July 13-26, 2023. The total population was the third-grade students of Widya Nusantara University about 119 and the total sample was about 54 samples. The results of research using the Kolmogorov-Smirnov alternative test, about 26 respondents (48.2%) who are active social media users and about 32 respondents (59.3%) have good sleep quality with p-value = 0.023 (p = <0.05). The conclusion mentioned that have a correlation between the use of social media (gadgets) and the student’s quality of sleep at Widya Nusantara University. The suggestion of this research is that it could be used as a basis for developing further research with various new problems that are expected to improve health status, especially the student’s quality of sleep because good sleep quality could improve the stability of emotional